(3GdJPcQI aj Yde GdcdGes - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj,J (B468 (3g` s
(3ChdgG (B:s
(3ef Chd GdehLhO fMh GdNdGa ajg EdG eG TfY GHf GdRfOj Ydj ef CYQGV eLJeYg Ydi eG Mcj s
(3BNQgG (B:s
(3hCeG GdhLd agh MRf hNha jYJQa Hg UaQI aj GdhLg dRhGd iNQ GdOe Yfg hgPG HGdSYGOI hJhH GMcGegG ef GMcGe s
(3fGbU U` (B21(3,` (B33(3, (B88 (3, (B144(3, (B147 (3ef GdJUhjQs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B26 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B692s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs